157k views
3 votes
-3(2x-3)=-6+9 How do you solve?

2 Answers

0 votes

Answer:

Explanation:

do u have to like determine if its true or not or solve the question?

User Tien Nguyen Ngoc
by
5.7k points
3 votes
you’re given:
-3(2x-3)= -6+9

you need to use distributive property and multiply -3 into 2x and -3:
-6x+9= -6+9

now you should simply the right side by adding 9 to -6:
-6x+9=3

then you need to subtract 9 from both sides in order to isolate the x term:
-6x= -6

then you divide both sides by -6 in order to get x by itself:
x=1
User MrEricSir
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.